Relação de fatores clínicos, candida spp., e-caderina e vimentina com alterações displásicas na leucoplasia oral - Eidt, João Matheus Scherbaum (2018)
Leukoplakia is the most prevalent potentially malignant lesion in the oral cavity, and histopathological examination is the gold standard for its diagnosis. Even though epithelial dysplastic features can be an indicator of malignant potential in oral leukoplakia, the exact determination of the grade of dysplasia is a hard task, which compromises this predictive factor. Therefore, predicting malignant transformation of oral leukoplakia is a challenge, and specific biomarkers are necessary for this purpose. The aim of the present study was to investigate the relationship of dysplastic changes in oral leukoplakia and clinical factors, Candida spp., and E-cadherin and vimentin expression. Medical records and paraffin blocks of biopsied specimens of 60 patients were distributed into 4 groups: (1) nodysplasia: 15 cases of leukoplakia without epithelial dysplasia; (2) epithelial dysplasia: 15 cases of leukoplakia with epithelial dysplasia (moderate or severe); (3) oral squamous cell carcinoma (OSCC): 15 cases of leukoplakia with histopathological diagnosis of OSCC; and (4) control group: 15 cases of fibroepithelial hyperplasia. Medical records were reviewed regarding age, sex, alcohol and tobacco use, and anatomical site of the lesion. Immunohistochemical analysis was carried out for determination of E-cadherin and vimentin expression, and periodic acid of Schiff (PAS) staining for Candida spp. detection. High-risk sites showed association with the epithelial dysplasia and OSCC groups. There was no significant difference between the groups for the other clinical features analyzed and for Candida spp. positivity with PAS. Quantitative E-cadherin expression did not significantly differ between the groups analyzed. Vimentin expression was significantly greater in the epithelial dysplasia and OSCC groups than the others. Conclusion: According to our results, high-risk sites (border/ventral surface of the tongue and floor of the mouth) are associated with the dysplastic phenotype of leukoplakia, whereas age, sex, alcohol, tobacco and Candida spp. do not show such association. Vimentin expression is associated with the oral dysplastic epithelial phenotype and it seems to be more specific than E-cadherin for use as an immunohistochemical marker to detect such alterations.